2021
DOI: 10.3390/su13042100
|View full text |Cite
|
Sign up to set email alerts
|

Towards Circular Social Housing: An Exploration of Practices, Barriers, and Enablers

Abstract: The concept of Circular Economy (CE) and its application in the built environment is an emerging research field. Scholars approach CE from various perspectives covering a wide range of topics from material innovation to city-scale application. However, there is little research on CE implementation in housing stock, particularly that which is managed or owned by the social housing organisations (SHOs) and which offers opportunities to generate circular flows of materials at the portfolio level. This research fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 67 publications
1
27
0
Order By: Relevance
“…CE strategies have been summarised under four categories of principles: narrowing resource loops (i.e., using fewer resources per product), slowing resource loops (i.e., keeping products in use as long as possible), closing resource loops (i.e., recycling materials) and regenerating resource loops (i.e., using renewable resources and regenerating the natural environment) ( Bocken et al., 2016 ; Konietzko et al., 2020 ; McDonough and Braungart, 2010 ; Stahel, 2010 ). In recent years, many studies have explored how CE strategies can be applied to buildings, henceforth referred to as ‘circular building strategies’ ( Çetin et al., 2021 ; Eberhardt et al., 2020 ; Guerra et al., 2021 ; Malmqvist et al., 2018 ; Pomponi and Moncaster, 2016 ). These studies have identified various strategies relevant to different life cycle stages of buildings.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…CE strategies have been summarised under four categories of principles: narrowing resource loops (i.e., using fewer resources per product), slowing resource loops (i.e., keeping products in use as long as possible), closing resource loops (i.e., recycling materials) and regenerating resource loops (i.e., using renewable resources and regenerating the natural environment) ( Bocken et al., 2016 ; Konietzko et al., 2020 ; McDonough and Braungart, 2010 ; Stahel, 2010 ). In recent years, many studies have explored how CE strategies can be applied to buildings, henceforth referred to as ‘circular building strategies’ ( Çetin et al., 2021 ; Eberhardt et al., 2020 ; Guerra et al., 2021 ; Malmqvist et al., 2018 ; Pomponi and Moncaster, 2016 ). These studies have identified various strategies relevant to different life cycle stages of buildings.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, circular building strategies have been applied and tested in numerous building projects in practice (e.g., Upcycle Studio, Circle House, etc.). Applying circular building strategies in practice faces many barriers ( Bilal et al., 2020 ; Çetin et al., 2021 ; Guerra et al., 2021 ; Hart et al., 2019 ) and requires significant innovation efforts to meet the functional, aesthetic, financial, process, and legal requirements in building development, construction, and management ( Hart et al., 2019 ). One barrier to initiating such innovation efforts has been a lack of knowledge regarding the environmental performance and related benefits of the various strategies ( Andersen et al., 2020 ; De Wolf et al., 2020 ; Eberhardt et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By the same dynamics, since companies need to invest in the transition process, the economic aspects appear as obstacles (O3), but they can be understood as catalysts when there are financial resources available or cost reductions (C8) [21,40,41,45,46,50,52]. This point further justifies studies on the attractiveness of businesses to receive investments.…”
Section: Discussionmentioning
confidence: 99%
“…Although benefits may shape a drive, determinants beyond what is perceived as technical and innovation-oriented may aid a digital transformation from within an organisation (Zulu and Khosrowshahi, 2021). Generally, scholars echo the complications and ambiguities behind driving innovations in the construction context (Akinade et al ., 2020; Çetin et al ., 2021). This becomes even more evident with the lack of a rationale that justifies innovation adoption (Newton and Newman, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%